Creating effective digital promotion and sales channels in online education: case of preparation for Unified National Testing in Kazakhstan (B2C) - Ibullayev, Zh. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Open education platforms have found their popularity in European countries since about 2012. The first open education systems began to function on the basis of global platforms such as Coursera, OpenEdx, etc. A distinctive feature of open systems was the ability to study for free at any time and from any place. This study includes methods of using effective channels of promotion and sales in the market of Kazakhstan. The dissertation consists of an introduction, literature review, data analysis and conclusion. The work includes 2 tables and 5 diagrams
Keywords: Unified National Testing in Kazakhstan, Online learning, Sales channel, Digital promotion